2021
DOI: 10.1055/a-1330-8765
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of a Semisolid Emulsion Containing Leptospermum scoparium Essential Oil and Evaluation of In Vitro Antimicrobial and Antibiofilm Efficacy

Abstract: Manuka oil, an essential oil derived from the Leptospermum scoparium, has been traditionally used for wound care and as a topical antibacterial, antifungal, and anti-inflammatory. However, the essential oil is not well retained at mucosal sites, such as the oral cavity, where the benefits of the aforementioned properties could be utilized toward the treatment of persistent biofilms. Within this study, L. scoparium essential oil was incorporated into a semisolid emulsion for improved delivery. The safety profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…[110] The main anti-F. nucleatum components in EOs are monoterpenes: sabinene, menthone, and carvacrol; γ-terpinene and sesquiterpenes: α-and β-selinene, germacrene, and viridiflorol (Table 1). [111][112][113][114][115] Grenier et al investigated the effects of EOs from three plants: Labrador tea (Rhododendron groenlandicum Kron & Judd), peppermint (Mentha x piperita L.), and winter savory (Satureja montana L.), on inhibiting F. nucleatum growth and biofilm formation. [111] Their research reported the chemical composition of the three EOs used in the study in terms of volatile components.…”
Section: Oxapampa Propolis Flavonoidsmentioning
confidence: 99%
“…[110] The main anti-F. nucleatum components in EOs are monoterpenes: sabinene, menthone, and carvacrol; γ-terpinene and sesquiterpenes: α-and β-selinene, germacrene, and viridiflorol (Table 1). [111][112][113][114][115] Grenier et al investigated the effects of EOs from three plants: Labrador tea (Rhododendron groenlandicum Kron & Judd), peppermint (Mentha x piperita L.), and winter savory (Satureja montana L.), on inhibiting F. nucleatum growth and biofilm formation. [111] Their research reported the chemical composition of the three EOs used in the study in terms of volatile components.…”
Section: Oxapampa Propolis Flavonoidsmentioning
confidence: 99%